The Animal Sacrifices and their Presentation Ritual by the Punics - saidi215, Salim (The Algerian Historical Journal, 2026)
The sacrifices are regarded as the most eminent spread religious manifestations into the ancient people, who used to do them often inside the temples in an individual or collective form according to special rituals and ceremonies and in various occasions like: thanks to the Gods or to collect an abundant harvest or to avoid a prompt danger. Whereas; in the Punic religion the animal sacrifices are the most important and present; it was regarded as an extension of the phonenician. Religion with some minor changes that occurred over time. It also knew some foreign influences coming from pharaonic Egypt and ancient Iraq.